Pengaruh ISO 14001, Kinerja Lingkungan, Green Accounting, dan Struktur Modal - Shinta Nurriya Istiqomah; Virna Sulfitri (CV. ITTC INDONESIA, 2026)
Environmental issues have become a global concern due to the increasing impacts of climate change, deforestation, and ecosystem degradation. In Indonesia, the energy sector is recognized as one of the major contributors to environmental damage, prompting growing pressure on companies to adopt sustainable business practices as a strategy to enhance firm performance and long-term competitiveness. This study aims to examine the effect of ISO 14001 certification, environmental performance, green accounting, and capital structure on the firm performance of energy sector companies listed on the Indonesia Stock Exchange. This research employs a quantitative approach using panel data analysis. The population consists of all energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Using purposive sampling, 230 firm-year observations were obtained. Data were collected from companies’ annual reports and sustainability reports, PROPER ratings issued by the Ministry of Environment and Forestry, and secondary data from the Indonesia Stock Exchange website. Hypothesis testing was conducted using panel data regression with the Fixed Effect Model. The results indicate that environmental performance and capital structure have a significant effect on firm performance. In contrast, ISO 14001 certification and green accounting do not show a significant effect on firm performance. These findings imply that actual environmental performance improvements and effective capital structure management play a more crucial role in enhancing firm performance than formal environmental certifications or disclosure-based environmental accounting practices.